2012
DOI: 10.1029/2012jc008170
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the barotropic and internal tides in a high‐resolution global ocean circulation model

Abstract: [1] Global comparisons of barotropic and internal tides generated in an eddy-resolving ocean circulation model are made with tidal estimates obtained from altimetric sea surface heights and an altimetry-constrained tide model. As far as we know, our Hybrid Coordinate Ocean Model (HYCOM) simulations shown here and in an earlier paper are the only published high-resolution global simulations to contain barotropic tides, internal tides, the general circulation, and mesoscale eddies concurrently. Comparing the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(162 citation statements)
references
References 25 publications
7
155
0
Order By: Relevance
“…Conversion rates (C) and energy fluxes (F E ) are particularly useful parameters in numerical models accounting for ITs and have been found to be good indicators in global circulation models and in several other independent studies (see e.g. Gerkema et al, 2004;Shriver et al, 2012;Jeon et al, 2014;Kang and Fringer, 2012). Despite detailed numerical simulations being beyond the scope of the present study, we note that preliminary results (following from Buijsman et al, 2016) proved very useful in identifying IT sources and their spatial distributions.…”
Section: Semi-diurnal Generation At the Amazon Shelf Breakmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversion rates (C) and energy fluxes (F E ) are particularly useful parameters in numerical models accounting for ITs and have been found to be good indicators in global circulation models and in several other independent studies (see e.g. Gerkema et al, 2004;Shriver et al, 2012;Jeon et al, 2014;Kang and Fringer, 2012). Despite detailed numerical simulations being beyond the scope of the present study, we note that preliminary results (following from Buijsman et al, 2016) proved very useful in identifying IT sources and their spatial distributions.…”
Section: Semi-diurnal Generation At the Amazon Shelf Breakmentioning
confidence: 86%
“…This particular data set is computed in a similar fashion as to Buijsman et al (2016), whose detailed description may be found in Metzger et al (2010), and Shriver et al (2012). According to the SAR data we seek a priori to establish a semi-diurnal generation for the IT, whose energy budget is therefore extracted from HYCOM simulations with a cut-off period between 9 and 15 h. These bandpass-filtered data are then used to compute the main IW field energetics, which will be discussed in the following paragraphs.…”
Section: Semi-diurnal Generation At the Amazon Shelf Breakmentioning
confidence: 99%
“…The HYCOM simulation examined in this study has geopotential tidal forcing for M 2 , S 2 , N 2 , and K 2 (the four largest semidiurnal constituents) and for K 1 , O 1 , P 1 , and Q 1 (the four largest diurnal constituents), a scalar self‐attraction and loading correction (SAL) [ Ray , ], and a parameterized topographic wave drag [ Arbic et al ., ; updated as described in Shriver et al ., ] with 32 layers in the vertical and a nominal horizontal resolution of 1/12.5° at the equator. For the tides, the model has only two adjustable parameters, the scalar SAL coefficient, and a topographic drag amplification factor.…”
Section: Modelmentioning
confidence: 99%
“…Shriver et al . [] find that the global barotropic tides in HYCOM compare well with an altimetry‐constrained barotropic tide model (TPXO) [ Egbert et al ., ] and that the model global internal tide amplitudes compare well with an altimetric‐based tidal analysis [ Ray and Byrne , ]. The multiyear length of this simulation (2005–2009) and its high horizontal resolution (1/12.5°) allow us to address the question: how stationary are the predicted internal tides as simulated in HYCOM?…”
Section: Introductionmentioning
confidence: 99%
“…The mode-1 internal tide has the longest vertical length and fastest phase speed, and may propagate over a long distance and redistribute the internal tidal energy in the open ocean [Ray and Cartwright, 2001;Merrifield et al, 2001;Dushaw, 2002;Alford, 2003;Zhao et al, 2010;Shriver et al, 2012]. Field measurements on the Dongsha Plateau revealed the presence of both the diurnal and semidiurnal internal tides, which are believed to come from the Luzon Strait [Duda et al, 2004;Duda and Rainville, 2008].…”
Section: Introductionmentioning
confidence: 99%